Self-Management and Social Innovation in Times of Crisis: Analysis of the «El tambo» Project (Lima, Peru) - Baltazar Diaz, Ana Claudia (2022)
The context of the Covid-19 pandemic evidenced a health, economic, and social system crisis, heavily impacting Peruvian citizens. Social groups and inhabitants of vulnerable areas founded initiatives to resist the pandemic collectively. One of them was El Tambo project, located in Villa María del Triunfo (Lima) which was executed by the residents of El Pedregal (human settlement), with volunteers from Killari and Entre Arquitectos social groups. The objective was to support families in El Pedregal, attend to their food needs, empower them to start managing their economic resources through a communal bakery and a Solidarity Feeding dining room. This research focuses on analyzing the community self-management process of the «El Tambo - Killari» project during the Covid-19 health crisis.